The white dwarf luminosity functions from the Pan–STARRS 1 3π Steradian Survey. Issue 1 (8th October 2018) - Lam, Marco C; Hambly, Nigel C; Rowell, Nicholas; Chambers, Kenneth C; Goldman, Bertrand; Hodapp, Klaus W; Kaiser, Nick; Kudritzki, Rolf-Peter; Magnier, Eugene A; Tonry, John L; Wainscoat, Richard J; Waters, Christopher
Abstract: A large sample of white dwarfs is selected by both proper motion and colours from the Pan-STARRS 1 3π Steradian Survey Processing Version 2 to construct the white dwarf luminosity functions of the discs and halo in the solar neighbourhood. Four-parameter astrometric solutions were recomputed from the epoch data. The generalized maximum volume method is then used to calculate the density of the populations. After removal of crowded areas near the Galactic plane and centre, the final sky area used by this work is 7.833 sr, which is 83 per cent of the 3π sky and 62 per cent of the whole sky. By dividing the sky using Voronoi tessellation, photometric and astrometric uncertainties are recomputed at each step of the integration to improve the accuracy of the maximum volume. Interstellar reddening is considered throughout the work. We find a disc-to-halo white dwarf ratio of about 100.